Robot modeling and kinematics - Manseur, Rachid (Da Vinci Engineering Press, 2006)
The book provides an introduction to robotics with an emphasis on the study of robotic arms, their mathematical description, and the equations describing their motion. It teaches how to model robotic arms efficiently and analyze their kinematics. The kinematics of robot manipulators is also presented beginning with the use of simple robot mechanisms and progressing to the most complex robot manipulator structures